Pengaruh Komposisi Media Tanam dan Konsentrasi Zat Pengatur Tumbuh terhadap Pembibitan Tebu (Saccharum officinarum L.) dengan Teknik Bud Chip - Krisnarini; Ana Wulandari; Yatmin; Windu Mangiring; Alima Maolidea Suri; Priyadi (Politeknik Negeri Lampung, 2026)
The bud chip technique is an important method in sugarcane propagation, as it enables the production of a large number of seedlings while using less planting material. However, the small size of the bud cuttings results in limited nutrient reserves and endogenous hormones, which may constrain early seedling growth. Therefore, optimizing the composition of the growing media and applying plant growth regulators (PGRs) are necessary to enhance seedling growth and development.This study employed a factorial Randomized Complete Block Design (RCBD). The objectives were to determine: (1) the appropriate composition of growing media for sugarcane seedlings using the bud chip technique; (2) the effects of different concentrations of plant growth regulators (PGRs) on seedling growth; and (3) the interaction between growing media composition and PGR concentration on the growth of sugarcane seedlings. The results indicated that: (1) the use of topsoil combined with cow manure, as well as topsoil combined with cow manure and rice husk compost, resulted in comparable seedling growth, both of which were superior to the control, as reflected in shoot height, leaf number, and shoot-to-root ratio. However, no significant differences were observed among treatments in terms of time to 50% sprouting and growth percentage; (2) different concentrations of PGRs did not significantly affect seedling growth across all observed variables; and (3) no interaction was found between growing media composition and PGR concentration on sugarcane seedling growth.